2007
DOI: 10.1530/eje-07-0032
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of sex steroids, sex hormone-binding globulin, and non-vertebral fractures in women and men: the Tromsø Study

Abstract: Objectives: As bone fragility is partly the result of sex hormone deficiency, we sought to determine whether circulating sex steroids or sex hormone-binding globulin (SHBG) predicts non-vertebral fractures. Methods: Forearm bone mineral density (BMD), total estradiol and testosterone, calculated free levels, and SHBG were measured in 1386 postmenopausal women and 1364 men aged 50-84 years at baseline in the Tromsø Study (1994)(1995). Non-vertebral fractures were documented between 1994 and 2005. Results: Durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
50
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(54 citation statements)
references
References 50 publications
(73 reference statements)
4
50
0
Order By: Relevance
“…Neither serum E2 nor serum T predicted risk of fractures in the Rotterdam study, which included 45 men with vertebral fractures, 54 or in the Troms ö study, which included 105 men with non-vertebral fractures. 55 An 18-year followup of the Framingham study, which included 39 men with hip fractures, showed that low E2, but not low T, was a predictor of fracture risk. 56 By contrast, from the Dubbo Osteoporosis epidemiology study, which included 113 men with fractures, it was reported that serum levels of T, but not E2, predicted the risk of fractures.…”
Section: Sex Steroids and Bone Health In Men C Ohlsson Et Almentioning
confidence: 99%
“…Neither serum E2 nor serum T predicted risk of fractures in the Rotterdam study, which included 45 men with vertebral fractures, 54 or in the Troms ö study, which included 105 men with non-vertebral fractures. 55 An 18-year followup of the Framingham study, which included 39 men with hip fractures, showed that low E2, but not low T, was a predictor of fracture risk. 56 By contrast, from the Dubbo Osteoporosis epidemiology study, which included 113 men with fractures, it was reported that serum levels of T, but not E2, predicted the risk of fractures.…”
Section: Sex Steroids and Bone Health In Men C Ohlsson Et Almentioning
confidence: 99%
“…In cross-sectional studies, inverse associations between both serum E 2 (44,56) and T (44) and prevalent fractures have been shown. Still, the roles of serum E 2 and T as predictors of fracture risk in men analyzed in large prospective studies remain contradictory (57)(58)(59)(60). Previous conflicting results might be due to the fact that these earlier prospective studies have been underpowered, including few incident fractures, and most of them (57-59) have analyzed the baseline sex steroid levels using immunoassay-based techniques, which have been shown to have a questionable specificity, especially at lower concentrations.…”
Section: Serum E 2 and Fractures In Menmentioning
confidence: 99%
“…Differently from the majority of studies, the CHAMP study did not find any association among serum T, E2, SHBG, and bone health, 122 on one hand, and, on the other hand, the Tromsø did not find any association between sex steroids and both BMD 71 and fracture risk. 72 Low total T levels were associated with lower hemoglobin levels in the InCHianti study similarly to EMAS, 89 suggesting that the effects of low T on hemoglobin should be carefully evaluated in older men due to the fact that anemia is one of the strongest markers of frailty 69 Not all studies investigated physical performance and both the muscular mass and strength in relation to circulating sex steroids. 77,123,124 (Table 3).…”
Section: Main Outcomes Of Cohort Studiesmentioning
confidence: 92%
“…For the majority of men, measurements of total T, E 2 and SHBG serum levels were available, even though the main aim of the study was not strictly related to hormonal changes overtime [66][67][68][69][70] (Table 2). The Tromsø study (https://en.uit.no/prosjekter/ prosjekt?p_document_idD80172) is composed by several surveys performed in sequence and collecting information that have changed overtime across different surveys 60,71,72 The fourth survey was taken between 1994 and 1995; all inhabitants of Tromsø (Northern Norway) older than 24 y were invited and, between the subjects who accepted to take part to the study, all men aged 55-74 y and random samples of the other age groups were involved and hormonal measurements performed 60 ( Table 2). The CHAMP study was originally designed in order to investigate the health status in men older than 70 y living in a defined geographical region near the Concord Hospital in Sydney.…”
Section: Main Characteristics Of Large Cohort Studiesmentioning
confidence: 99%